Human toxoplasmosis in Kuna and Embera children in the Bayano and San Blas (2022)
eng: We conducted a survey of 760 Amerindian children 2-12 years of age in the Bayano and San Blas areas of Panama in 1991 to determine the prevalence of serum antibodies to Toxoplasma gondii and the importance of hypothesized risk factors in human-induced native and sylvatic conditions, which have had few environmental changes, as opposed to rural and urban areas in Panama previously studied. The overall prevalence of infection ranged between 0% and 42.5%. No age curve was detected, indicative of nonconstant transmission. Only two hypothesized risk factors, floor type and having cats inside the house, were significantly associated with the presence of antibodies in some of the communities. Antibody prevalence appeared to be associated more with the community of residence than with any specific behavior. The risk factor of importance may be the level of oocyst contamination, since infection by tissue cysts in meat was excluded. On three of the nine islands studied, no antibody was detected in the children or the cats. It would appear that T. gondii is not present on these islands. Although the data did not support the importance of many of the hypothesized risk factors, the study is consistent with the theory of transmission by oocysts and the importance of cats in transmission.